Nurse perceptions of a nurse family liaison implemented during the COVID-19 pandemic: A qualitative thematic analysis. (June 2022) - Keen, Alyson; George, Annie; Stuck, B.T.; Snyder, Colby; Fleck, Kyle; Azar, Jose; Kara, Areeba
Highlights: Major themes identified from implementation of a nurse family liaison were living in a pandemic, establishing the role and workflow, and experiencing human connection. Participants described both fulfillment from their unique contributions during the COVID-19 pandemic and the burden of bearing witness to grief and loss. The liaison ensured that the family was cared for, allowing the bedside nurses to focus on high quality care for the patient without guilt or distress lingering due to unmet family needs. Abstract: Objective: Stress among family members of hospitalised intensive care unit patients may be amplified in the context of a global pandemic and strict visitor restrictions. A nurse family liaison role in the COVID-19 units was implemented to serve as a connection between the care team and a designated family member. Our objective was to describe the experience of a nurse family liaison role implemented during the COVID-19 pandemic from the perspective of nurses who functioned in the liaison role and intensive care nurses who worked with the liaisons. Research method/design: This was a qualitative study using thematic analysis involving a one-time semi-structured interview. A convenience sample of nurses were invited to participate. The analytic approach involved (1) becoming familiar with the data; (2) finding meaning in the data; (3) organising meaningful statements into patterns to generate themes. Setting/participants: Nurses who functioned in the liaison role and intensive care nurses who worked with the liaisons in an adult academic health center in the Midwest United States. Main outcome measure: To describe the psychosocial experience of nurse family liaison role implementation. Findings: The sample (n = 11) mean age was 36 years (range 26–49) and the majority were female (n = 10; 90%), White/non-Hispanic (n = 11; 100%), Bachelor prepared (n = 10; 90%), and had an average of 10 years of experience as a nurse (range 4–25). The major themes identified by participants were living in a pandemic, establishing the role and workflow and experiencing human connection. Conclusion: Hospital organisations should consider how they can provide family-centred care, specifically within the context of a global crisis such as a pandemic. Participant descriptions of the role indicate that liaison implementation alleviated nurse moral distress and fostered development of close family connections. Findings can help inform implementation of similar roles in hospital settings.